Cell-type specific variation in the induction of ER stress and downstream events in chikungunya virus infection. (December 2016) - Khongwichit, Sarawut; Wikan, Nitwara; Abere, Bizunesh; Thepparit, Chutima; Kuadkitkan, Atichat; Ubol, Sukathida; Smith, Duncan R.
Abstract: Over the last decade infections with the mosquito transmitted chikungunya virus (CHIKV) have become a major worldwide concern, and considerable efforts have been made in understanding the interaction of this virus with the host cell machinery. Studies have documented the induction of the unfolded protein response (UPR), as well as the induction of apoptosis and autophagy in response to CHIKV infection. This study comparatively analysed these three processes in two cell lines, Hela and HepG2. Infection of Hela cells was characterized by activation of the PERK/eIF2α branch of the UPR, the induction of autophagy and early apoptosis, while infection of HepG2 cells was characterized by activation of the IRE/XBP1 branch of the UPR, limited or no activation of autophagy and comparatively later apoptosis. These results show that the specific cell context is an important mediator of the host cell response to CHIKV infection. Highlights: Host cellular pathways were examined in chikungunya virus infection of two cell lines. Activation of different branches of the unfolded protein response was observed. Cell context is a mediator of the host cell response to chikungunya virus infection.